(3CSGfjO bQGAI GdCghGRis - (3GdMSf Hf Ydj Hf EHQGgje Hf jROGO GdCghGRj, CHh Ydj,J (B446 (3g` s
(3ChdgG (B:s
(3QhGjI bGdhf GdGghGRi Ydi GdGeGe CHj GdMSf Ydi GdMSf Ydi YHO GdMejO GdSejTGWi GdHUQi SfI KdGK hKdGKjf hKdKeGFI s
(3BNQgG (B:s
(3GdGghGRi Ydi GdSWhi Ydi GHf eLGgO CHj QHjYg hYdi CHj GdMHGfi GdMOGO cdGgeG Ydi GdaQi s
(3HBNQgG hbajIs
(3HgG fXGe GdJYbjHIs
(3bQCgG GdcGJH Ydi GdTjN CMeO GdeSjQi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B247s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2004s
Keywords: (3GdbQGAGJ hGdJLhjOs